2020
DOI: 10.1186/s13071-020-04183-2
|View full text |Cite
|
Sign up to set email alerts
|

First evidence of the mutations associated with pyrethroid resistance in head lice (Phthiraptera: Pediculidae) from Honduras

Abstract: Background: The human head louse, Pediculus humanus capitis, is a cosmopolitan blood-sucking ectoparasite affecting mostly schoolchildren in both developed and developing countries. In Honduras, chemical pediculicides are the first line of treatment, with permethrin as their main active ingredient. Despite the extended use of these products, there is currently no research investigating insecticide resistance in Honduran head lice. In head lice, the most common mechanism is knockdown resistance (kdr), which is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 37 publications
0
24
0
Order By: Relevance
“…Having excess of homozygotes is an indicator of inbreeding or in fixation of mutant alleles. On the contrary, the first study of pyrethroid resistance in head lice from Honduras by Larkin et al [ 20 ] using RFLP techniques have demonstrated that the majorities of head lice had excess of heterozygotes of kdr -type mutations which indicates the active selective pressure among head lice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Having excess of homozygotes is an indicator of inbreeding or in fixation of mutant alleles. On the contrary, the first study of pyrethroid resistance in head lice from Honduras by Larkin et al [ 20 ] using RFLP techniques have demonstrated that the majorities of head lice had excess of heterozygotes of kdr -type mutations which indicates the active selective pressure among head lice.…”
Section: Discussionmentioning
confidence: 99%
“…The knockdown resistance (kdr), due to the three-point mutation (amino acid substitutions on the M815I, T917I, and L920F) can be identified on the α-subunit of voltage sensitive sodium channel (VSSC) gene [15][16][17]. Several reports suggested that M815I and L920F mutations reduce susceptibility to permethrin [18][19][20], whereas for the T917I mutation, whenever present, whether in alone or combination with L920F mutation, the mutation plays an important role in permethrin resistance and can be used as a molecular biomarker for head lice permethrin or pyrethroid resistance [21,22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 ). 94 , 95
Figure 8 Pediculus humanus capitis . Causal agent of pediculosis of the scalp, endemic in large urban agglomerations.
…”
Section: Environmental Degradationmentioning
confidence: 99%
“…Regarding primary school children in Thailand, kdr T9171 and L920F point mutations were discovered in permethrin-resistant head lice [ 13 ]. In Honduras [ 14 ], Chile [ 15 ], and Madagascar [ 16 ], the T917I kd r allele was found in head lice resistant to pyrethroid insecticides. However, in Senegal, it has been reported that the presence of a point mutation of GluCI is associated with ivermectin-resistant head lice [ 17 ].…”
Section: Introductionmentioning
confidence: 99%